(untitled) (Revista Contexto & Educação, 2021)
This article aims to analyze the perspectives of human formation present in the education proposal implemented through the Interactive Educational System in Pará. The research was carried out through bibliographic and documentary research. The main theorists that support the analysis are: Frigotto (2010), Saviani (2013, 1982), Kosic (2011), Fereira (2015), Angeli (2009). The Interactive Educational System, besides not potentialize human training, further deepens social and regional inequalities by promoting a dualist urban/ rural educational policy, fragmented and doubtful quality, ineffective in the development of omnilateral training for populations that have historically denied their right of access to knowledge produced by humanity. The teaching methodology used to access of High school in rural communities, through the Interactive Educational System, contributed little to the reflection of the concrete reality of these subjects and consequently for their transformation.